A comparative analysis of the different CNN-LSTM model caption generation of medical images - Amin, Mahzabin Yasmin Binte; Shammo, Weney Hasan; Sayed, Jawad Bin; Hossain, MD Junaied (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.